Arabic Seminar-Based Curriculum Development For Enhancing Transnational Da'wah Competencies In Female Islamic Boarding Schools - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (CV Putra Publisher, 2025)
This study examines the role of Arabic language seminars in curriculum development for strengthening global da‘wah competencies among female students at Pondok Modern Darussalam Gontor (PMDG) Putri Campus 1. The research employed a qualitative case study approach involving observations, semi-structured interviews, and documentation analysis. The participants consisted of Arabic language teachers, seminar organizers, invited speakers, and female students participating in the Arabic Language Seminar commemorating the centenary of Gontor. The findings reveal that the seminar functioned not merely as an academic event but as a strategic instrument of curriculum enrichment within the pesantren educational system. The seminar contributed significantly to strengthening students’ communicative confidence, intercultural awareness, and global Islamic orientation through authentic language interaction and experiential learning practices. Furthermore, the seminar reflected the transformation of Arabic curriculum development in pesantren toward integrative and competency-based educational models that combine Islamic values, language mastery, and global engagement. This study contributes theoretically to the discourse of curriculum development in Islamic education by positioning academic seminars as part of hidden curriculum and educational culture in pesantren. Practically, the findings suggest that Islamic boarding schools should integrate collaborative and globally oriented academic programs into Arabic language education to prepare students for contemporary da‘wah challenges.